2005
DOI: 10.1016/j.ejvs.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Prevention of Atherosclerosis Through Chlamydia pneumoniae Eradication (SPACE Trial): A Randomised Clinical Trial in Patients with Peripheral Arterial Disease

Abstract: A short-term course of azithromycin offers no benefits for survival or ankle pressure in PAD-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 53 publications
(74 reference statements)
0
14
0
1
Order By: Relevance
“…[175][176][177][178] Four studies enrolled Ϸ1300 patients; 3 of the 4 studies demonstrated no benefit in peripheral artery disease-related outcomes among antibiotic recipients. In the absence of evidence supporting improved outcomes, there has been no recommendation from professional societies for antibiotic therapy in the absence of sepsis for patients with MI, unstable angina, peripheral artery disease, or asymptomatic coronary artery disease.…”
Section: Direct Mechanisms: Bacteremia and Vascular Infection By Perimentioning
confidence: 99%
“…[175][176][177][178] Four studies enrolled Ϸ1300 patients; 3 of the 4 studies demonstrated no benefit in peripheral artery disease-related outcomes among antibiotic recipients. In the absence of evidence supporting improved outcomes, there has been no recommendation from professional societies for antibiotic therapy in the absence of sepsis for patients with MI, unstable angina, peripheral artery disease, or asymptomatic coronary artery disease.…”
Section: Direct Mechanisms: Bacteremia and Vascular Infection By Perimentioning
confidence: 99%
“…Intriguingly the results of the large randomized placebo-controlled clinical trials did not support the infectious agent hypothesis, consequently it was largely concluded that C. pneumoniae was not an important cofactor in AS and that efforts to treat C. pneumoniae with antimicrobials could not alter disease outcomes [4042]. However, the following observations could not be ignored.…”
Section: Endothelial Response To Injurymentioning
confidence: 99%
“…Thus, the data presented here fit a model of systemic infection with an intermediate step where bacterial strains, once in the circulation, are internalized by phagocytic cells, at which stage selected species avoid immediate killing and spread and colonize distant sites. Bacterial internalization may also account for the resistance to antibiotic treatment observed in large randomized placebo-controlled clinical trials for the secondary prevention of cardiovascular events 32) . To address the study limitations, the true causative role of this species in vascular pathologies using in vitro and in vivo models must be further investigated.…”
Section: Persistence In Phagocytesmentioning
confidence: 99%